2016
DOI: 10.1016/j.sbspro.2016.05.116
|View full text |Cite
|
Sign up to set email alerts
|

Does ISO 9001 Quality Certification Influence Labor Productivity in EU-27?

Abstract: Labor productivity stands between the main indicators assessing national economic conditions and contributing to the economic growth and welfare. This paper adds to the literature investigating the macroeconomic determinants of labor productivity, focusing on the role of the International Organization for Standardization (ISO) quality certification standards. For this purpose we employ a panel data framework for EU-27 countries for the period 2000-2013 and we address potential endogeneity and heteroskedasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Although ISO 9000 focuses on the quality process within an organization, it does not guarantee the quality of the product or service (Guler, et al, 2002). Several studies have shown that the implementation of the standards can improve the performance of an organization in terms of internal process: placing the quality at the center of the activities of an organization is likely to eliminate errors or to give a better staff commitment (Albulescu, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although ISO 9000 focuses on the quality process within an organization, it does not guarantee the quality of the product or service (Guler, et al, 2002). Several studies have shown that the implementation of the standards can improve the performance of an organization in terms of internal process: placing the quality at the center of the activities of an organization is likely to eliminate errors or to give a better staff commitment (Albulescu, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of ISO standards in implementing international trade was discussed in Borial [7] The possibilities of clustering European countries according to the extent of ISO 9001 certification were discussed in the works of Franceschini [8]. The analysis of the increased attention to ISO standards in other management areas was addressed in Berényi L. The impact of ISO 9001 standards on labor productivity was studied in the article by Albulescuab [9]. Research on integrated management systems in a country with a relatively low number of ISO 9001 and ISO 14001 certifications was conducted in the works by Bernardo [10]; Bouranta N. et al, [11].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Literature review shows that productivity is linked to many influencing factors, starting with R&D spending and innovations (Lopez-Rodriguez and Martinez-Lopez, 2017; Minniti and Venturini, 2017), structural changes in the economy (Duguleana and Duguleana, 2016;Harada, 2015;Hartwig, 2015;Maudos et al, 2008;Padilla-Pérez and Villarreal, 2017), ecological perspective (Yörük and Zaim, 2005;Mahlberg et al, 2011), industry innovation and productivity (Ivanova et al, 2017) and even quality management systems (Albulescu et al, 2016). Factors that influence productivity are related to technologies, knowledge, exclusive resources (specific natural resources), prices of the resources (labour, electricity etc.…”
Section: Productivity Influencing Factorsmentioning
confidence: 99%